Pengaruh Kecepatan Udara Primer dan Sekunder terhadap Kenerja Kompor Biomassa Berbahan Bakar Cangkang Kemiri - Sopyan Ali Rohman; Abdurrahman; Shafwan Amrullah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2022)
Household energy need in Indonesia, especially for cooking, are still dominated by LPG fossil fuels with 70% of LPG needs being imported. On the other hand, the availability of biomass waste, especially candlenut shells, is abundant. One way to optimize the use of candlenut shells is to use candlenut shells as fuel for biomass stoves by optimizing the efficiency of biomass stoves. In this study, a biomass stove with primary and secondary airflow was used with a combustion chamber diameter of 200 mm and a height of 340 mm. The biomass waste used is candlenut shells as fuel. The purpose of this study was to explain the increase in the performance of a biomass stove fueled with candlenut shell which is influenced by primary and secondary air velocity. Biomass stove testing includes thermal efficiency, specific fuel consumption, CO and CO2 emissions. The performance test results show that the biomass stove with a primary air velocity of 3.7 m/s, a secondary air velocity of 3.7 m/s has the highest thermal efficiency of 45.77%. The lowest specific fuel consumption is obtained from a biomass stove with a primary air velocity of 1.5 m/s, a secondary air velocity of 1.5 m/s, which is 0.583 kg/hour, and the emission test results show that complete combustion occurs with 0% CO emotion. on all air velocity variables studied.